Advancements in Electric Vehicle Technologies: A Review of Powertrain Architectures and Battery Innovations - Hasan Mia, Md Mehedi; Uddin, Md Jasim; Ahmed, Abu Sayed Faisal (Peneliti Teknologi Teknik Indonesia, 2025)
The main goal of this paper is to review the advancements in electric vehicle technologies for powertrain and battery innovations. The rapid evolution of electric vehicles (EVs) is driven by advancements in powertrain architecture and battery technologies, enabling improved efficiency, performance, and sustainability. This review explores recent innovations in EV powertrains, including permanent magnet synchronous motors (PMSMs), induction motors, and emerging switched reluctance motors (SRMs), along with advancements in motor control strategies and power electronics. Advanced control techniques like field-oriented control (FOC) and predictive control must be explained in detail for PMSM-based electric vehicle systems. FOC is a popular vector control method that converts the torque and flux components of the stator current into a rotating reference frame to decouple them. However, a more contemporary method called model predictive control (MPC) forecasts future system states using a dynamic model to optimize motor control operations. Additionally, battery technology developments, such as high-energy-density lithium-ion batteries, solid-state batteries, and next-generation fast-charging solutions, are analyzed in terms of energy storage capacity, charging speed, thermal management, and lifecycle improvements. The need for innovation is still shaped by practical obstacles in addition to technical developments in electric vehicle (EV) powertrains. Manufacturers are compelled to investigate alternative chemistries or optimize energy usage through more effective motor control and thermal management, for example, because lithium-ion batteries' reliance on rare and geopolitically sensitive materials like cobalt raises concerns about sustainability and the supply chain. The integration of powertrain and battery innovations with intelligent energy management systems and vehicle-to-grid (V2G) technology is also discussed, highlighting their impact on EV range, reliability, and grid sustainability. This review provides a comprehensive understanding of the current technological landscape and future directions in EV development, addressing key challenges such as material limitations, charging infrastructure, and cost-effectiveness.